Conversion of Methanol to Olefin Over Zeolite Based Catalysts: A Review - David Haruna, Amani; Umar Hambali, Hambali; Omotayo Abu, Taofiqat; Saleh, Andeyabin (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The increasing demand for olefins and continuous depletion of world oil reserves necessitated alternative routes to produce light olefins using non-petroleum feedstocks. Hence, MTO has attracted much attention; the conversion of methanol to olefin (MTO) has gained significant attention in the recent years due to potential in providing alternative routes for the production of valuable petrochemicals. Overall, this review offers a comprehensive analysis of conversion of methanol to olefins over zeolite-based catalysts. It provides valuable insight into current challenges and potential areas for future research, making it a useful resource for researchers, engineers and professionals working in the field of catalysis and petrochemical production.